Chemical-nutritional parameters and volatile profile of eggs and cakes made with eggs from ISA Warren laying hens fed with a dietary supplementation of extruded linseed - Andrea Ianni; Fiorentina Palazzo; Lisa Grotta; Denise Innosa; Camillo Martino; Francesca Bennato; Giuseppe Martino (Asian-Australasian Journal of Animal Sciences, 2020)
Objective The aim of this study was to evaluate the chemical-nutritional parameters, oxidative stability and volatile profile of eggs and cakes made with eggs from laying hens fed with a dietary supplementation of extruded linseed. Methods Two thousand ISA Warren laying hens were randomly divided into two groups: a control group was fed with a standard diet while the experimental group received the same diet supplemented with 7% of extruded linseed. The trial lasted 84 days, in which three samplings of laid eggs were performed. Samples of eggs and food systems arising from eggs were then analyzed in order to obtain information about β-carotene and total flavonoid content, antioxidant activity, fatty acid profile, lipid oxidation, and volatile profile. Results Linseed induced the increase of α-linolenic acid with consequent reduction of the ω-6/ω-3 ratio (4.3:1 in egg yolk); in addition to this, was evidenced the cholesterol reduction and the significant increase in total flavonoids and β-carotene, although no variations were detected in antioxidant capacity. Even in cooked products there was not only a direct effect of linseed in increasing α-linolenic acid, but also in inducing the reduction of cholesterol and its major oxidation product, 7-ketocholesterol. The dietary linseed integration was also shown to affect the volatile profile of baked products. Conclusion Data confirmed that dietary supplementation with extruded linseed resulted in food products with interesting implications for human health. With regard to the volatile profile of baked products it would be necessary undertake further sensorial analysis in order to evaluate any variations on flavor and consumer acceptability.